Pengaruh Prinsip-Prinsip Dasar Etika Terhadap Mendeteksi Kecurangan (Fraud) Pada Kantor Akuntan Publik Di Kota Medan - Fahmi, Muhammad; Hutahayan, Ariyan (Jurnal Riset Akuntansi dan Bisnis, 2024)
The purpose of this study is to examine and analyze the influence of basic ethical principles on detecting fraud at Public Accounting Firms in Medan City. The approach used in this research is an associative approach. The associative approach is a method that uses two or more variables to determine the relationship between one variable and another. The sample consists of 74 respondents, determined using the Slovin formula. The data collection technique in this study uses a questionnaire method. The data analysis techniques employed in this research include Path analysis, Partial Least Square (PLS), and Hypothesis Testing. Data processing in this study uses the Smart PLS 4.1 software to test the proposed hypotheses. The results show that the integrity and competence of auditors have a positive effect on detecting fraud.